#### Answer

$-4a^4b^3\sqrt {2b}$

#### Work Step by Step

$-\sqrt{32a^8b^7} =-\sqrt {16a^8b^6}\sqrt {2b}=-4a^4b^3\sqrt {2b}$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$-4a^4b^3\sqrt {2b}$

$-\sqrt{32a^8b^7} =-\sqrt {16a^8b^6}\sqrt {2b}=-4a^4b^3\sqrt {2b}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.